Reactive oxygen species in endothelial function - from disease to adaptation - Craige, Siobhan M; Kant, Shashi; Keaney, Jr, John F (Circulation journal : official journal of the Japanese Circulation Society, 2015)
Endothelial function is largely dictated by its ability to rapidly sense environmental cues and adapt to these stimuli through changes in vascular tone, inflammation/immune recruitment, and angiogenesis. When any one of these abilities is compromised, the endothelium becomes dysfunctional, which ultimately leads to disease. Reactive oxygen species (ROS) have been established at the forefront of endothelial dysfunction; however, more careful examination has demonstrated that ROS are fundamental to each of the sensing/signaling roles of the endothelium. The purpose of this review is to document endothelial ROS production in both disease and physiological adaptation. Through understanding new endothelial signaling paradigms, we will gain insight into more targeted therapeutic strategies for vascular diseases.